BENTUK KESANTUNAN BERBAHASA DALAM WACANA DIALOG KETOPRAK SAPTA MANDALA LAKON BABAD ALAS MENTAOK - Pramujiono, Agung (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
This study aimed at describing and explaining the phenomenon of linguistic politeness in dialogue discourse inKetoprak Sapta Mandala of in the play of Babad Alas Mentaok. This phenomenon needs to be studied becausepoliteness in this discourse is unique, particularly in the selection of forms and politenesss trategies. The study used thePoliteness Theory of Brown and Levinson (1987) with ethnopragmatic perspectives. Ethnopragmatics is aninterdisciplinary study of Pragmatics and Ethnographic of Communication. Data were taken from the recording ofKetoprak Sapta Mandala Ã¢â‚¬Å“Ratu Kidul Ã¢â‚¬Â episode of Ã¢â‚¬Å“Babad Alas Mentaok Ã¢â‚¬Â drama series by Fajar which isconverted into a digital format in website of jamansemono.com. It was then analyzed by using descriptive analysis following the interactive model of Miles and Huberman. Based on the analysis of data, it can be concluded thatutterances representing forms of politeness can be broken down into three categories: declarative (SUBDek),interrogative (SUBInt), and imperative (SUBImp) modes. SUBDek was realized in various forms of speech actsincluding (1) assertive speech acts: notifying and stating; and (2) expressives: thanking, expressing happiness,apologizing, praising, and criticizing. SUBInt was realized indirective speech acts, such as requesting information,confirming, and asking for permission. SUBImp realized indirective speech acts, for instance giving commands,allowing, prohibiting, and inviting. The politeness strategies used in the play discourse include direct strategies; positivepoliteness strategies with sub-strategies (1) giving attention, (2) giving praise, and (3) using a group marker; negativepoliteness strategies with sub-strategies(1) using speech of respect, (2) using indirect speech, and (3) using a variety ofmanners; and off-record/indirect strategies under taken by (1) using narrative strategies and (2) using implied speech.The use of narrative strategies as the indirect strategy constitutes a finding that can be used to complement the indirectsub-strategy proposed by Brown and Levinson (1987).